2007
DOI: 10.2353/ajpath.2007.060792
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Attenuated Plasmodium berghei Liver Stages Persist and Elicit Sterile Protection Primarily via CD8 T Cells

Abstract: Live-attenuated Plasmodium liver stages remain the only experimental model that confers complete sterile protection against malaria. Irradiation-attenuated Plasmodium parasites mediate protection primarily by CD8 T cells. In contrast, it is unknown how genetically attenuated liver stage parasites provide protection. Here, we show that immunization with uis3(؊) sporozoites does not cause breakthrough infection in T and B-cell-deficient rag1 ؊/؊ and IFN-␥ ؊/؊ mice.However, protection was abolished in these anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 33 publications
4
94
1
1
Order By: Relevance
“…Immunization of mice with uis3 Ϫ , uis4 Ϫ , or p52 Ϫ parasites induced complete, long-lasting protection against infectious sporozoite challenge (7-9, 11), demonstrating that rodent malaria GAPs are highly effective vaccines. The GAP-induced protection was mediated mainly by CD8 ϩ T cells (9,13,14), but antibodies also contributed to protection (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization of mice with uis3 Ϫ , uis4 Ϫ , or p52 Ϫ parasites induced complete, long-lasting protection against infectious sporozoite challenge (7-9, 11), demonstrating that rodent malaria GAPs are highly effective vaccines. The GAP-induced protection was mediated mainly by CD8 ϩ T cells (9,13,14), but antibodies also contributed to protection (9).…”
mentioning
confidence: 99%
“…Immunization of mice with uis3 Ϫ , uis4 Ϫ , or p52 Ϫ parasites induced complete, long-lasting protection against infectious sporozoite challenge (7-9, 11), demonstrating that rodent malaria GAPs are highly effective vaccines. The GAP-induced protection was mediated mainly by CD8 ϩ T cells (9,13,14), but antibodies also contributed to protection (9).To assess the potential to create a GAP vaccine for human malaria, we deleted the P52 and P36 loci in P. falciparum. The deletions did not affect the parasites throughout most of the life cycle, including sporozoite production of the attenuated lines, but resulted in significant growth defects in a hepatocytic cell line.…”
mentioning
confidence: 99%
“…It is approved that live-attenuated parasites with irradiation are protective to the host where the contents of parasites in red blood cells are low. However there was no boost conducted to the primed mice, as done by other researchers, to gain the higher degree of acquired immunity which is directly proportional to the number of immunizing doses [12]. Challenges with live parasites is also required to test whether the injection of attenuated parasites as vaccine materials could elicit an antibody in the host; it is the most relevant approach to testing the efficacy of experimental malaria vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that immunization with attenuated sporozoites induces humoral immune responses against Plasmodium antigens [29] and it was shown that repeated sporozoite challenges of vaccinated mice induce sporozoite-specific antibodies as well [30]. Therefore, we evaluated the contribution of sporozoite-specific antibodies to prolonged protection observed after sporozoite challenge.…”
Section: Induction Of Sporozoite-specific Antibodies Upon Sporozoite mentioning
confidence: 99%